THE EFFECTIVENESS OF THE "LANCIPMAS–PRESISIMAS" MNEMONIC STRATEGY ON JUNIOR HIGH SCHOOL STUDENTS' ACCURACY IN DISTINGUISHING PYRAMIDS AND PRISMS - Padri Ulfulqan Fulqan; Baidullah Baidullah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the effectiveness of the "LANCIPMAS–PRESISIMAS" mnemonic strategy in improving junior high school students' ability to accurately distinguish between pyramids and prisms. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research population consisted of all eighth-grade students of SMP Negeri 3 Susoh during the second semester of the 2025/2026 academic year. The sample was selected through purposive sampling and comprised one control class consisting of 19 students and one experimental class consisting of 20 students. The research data were collected through a multiple-choice achievement test administered during the pretest and posttest phases, supported by documentation. The data were then analyzed using descriptive and inferential statistics. Inferential analysis was conducted using Welch's t-test, followed by the calculation of the effect size using Glass's delta index with the aid of SPSS software. The results indicated a significant difference in learning outcomes between the two groups. The experimental class achieved a mean posttest score of 89.47, while the control class obtained a mean score of 50.68. Welch's t-test yielded a p-value of < 0.001, indicating that the difference was statistically significant. Furthermore, the Glass's delta value of 6.654 was classified as a very large effect. Based on these findings, it can be concluded that the "LANCIPMAS–PRESISIMAS" mnemonic strategy is effective in helping students reduce cognitive load, improve memory retention, and enhance their accuracy in distinguishing and understanding the concepts of pyramids and prisms.